928. Major Decrease in Prevalence of Hepatitis C Viremia in Key Populations following the Second Year of Treatment as Prevention for Hepatitis C (TraP HepC) Program in Iceland. (26th November 2018) - Gottfredsson, Magnus; Tyrfingsson, Thorarinn; Runarsdottir, Valgerdur; Hansdottir, Ingunn; Bergmann, Ottar M; Bjornsson, Einar S; Johannsson, Birgir; Sigurdardottir, Bryndis; Fridriksdottir, Ragnheidur H; Löve, Arthur; Löve, Thorvardur J; Sigmundsdottir, Gudrun; et al.
Abstract: Background: Hepatitis C Virus (HCV) commonly affects people who inject drugs (PWID) and/or with history of injection drug use (IDU). They are also disproportionately represented in addiction treatment centers and the penitentiary system. In order to curtail spread of HCV it is therefore important to approach these groups. PWID and prisoners have been prioritized in the TraP HepC program. The impact can thus be assessed by monitoring HCV prevalence at sentinel sites, such as addiction hospitals and prisons. Methods: TraP HepC offers direct-acting antiviral agents (DAAs) to all HCV patients in Iceland, starting in January 2016. HCV PCR is performed at the end of treatment and 12 weeks later (SVR12). PWID and prisoners are monitored for reinfection and retreated if needed. We compared the prevalence of HCV viremia among PWID admitted for treatment at Vogur addiction hospital and inmates of the penitentiary system, before and after 2 years of TraP HepC. Results: Two years into the program 667 patients had been evaluated of which 632 were initiated on their first course of DAAs and 7 were pending, representing 80% of the estimated total patient population. Of those who completed first treatment according to guidelines the SVR12 is 95.5%. Drop-out from first treatment was 8.2%; nevertheless, the SVR12 was >40% and most of the remaining viremic patients completed or are undergoing retreatment. In 2012–2015, prior to TraP HepC the prevalence of HCV viremia among actively injecting PWID admitted for addiction treatment was 47.9%, dropping to 39.8% in 2016 and 16.2% in 2017 ( P < 0.001). Likewise, the prevalence of viremia among patients with history of IDU but not recently injecting fell from 27.4% (2012–2015) to 19.8% in 2016 and 4.1% in 2017 ( P < 0.001). The prevalence of viremia among inmates of the penitentiary system was 29% prior to initiation of TraP HepC, dropping to 7% in 2017 ( P < 0.01). These results are not explained by declining IDU in the community. Conclusion: On a population level the domestic transmission of HCV can be reduced by DAAs when combined with other efforts. Two years into the TraP HepC program the prevalence of viremia among two of the most important drivers of the epidemic has been markedly reduced. The program is ongoing, with further emphasis on increased intensity of screening, retreatment and harm reduction. Disclosures: All authors: No reported disclosures.